2009
DOI: 10.1111/j.1865-1682.2009.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Microbiological and Molecular Typing Aspects of Paratuberculosis in Sheep and Goats in Northern Greece

Abstract: Mycobacterium avium subsp. paratuberculosis, an acid-fast bacterium is the agent of Johne's disease, an intestinal disease that causes poor nutrient intake in ruminants. During the period 1987-2003, 322 of 777 (41.4%) goat herds and 97 of 458 (21.1%) sheep flocks were found to be infected with M.a.paratuberculosis in Northern Greece. From goats, mycobacteria were isolated from 238 of 652 (36.5%) of intestinal tissues, 14 of 119 (11.8%) of lymph nodes and five of 369 (1.4%) of faecal samples. From sheep, mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…The low percentage of MAP isolation in this study was also observed in others, such as Dimareli-Malli et al (2009);Medeiros et al (2012) and Barad et al (2014), which corroborates the low sensitivity of the isolation technique to individual paratuberculosis diagnosis. Furthermore, MAP from subclinical animals due to intermittent disposal and low number of bacteria in feces and milk (Whipple et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The low percentage of MAP isolation in this study was also observed in others, such as Dimareli-Malli et al (2009);Medeiros et al (2012) and Barad et al (2014), which corroborates the low sensitivity of the isolation technique to individual paratuberculosis diagnosis. Furthermore, MAP from subclinical animals due to intermittent disposal and low number of bacteria in feces and milk (Whipple et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…Esses resultados são semelhantes aos obtidos por outros autores (Coelho et al 2007, Dimareli-Malli et al 2009), conϐirmando a baixa sensibilidade do isolamento para o diagnóstico individual de paratuberculose.…”
Section: Discussionunclassified
“…In Australia, the prevalence was estimated to be in the range of 2.4%–4.4% [48], while in northern Greece, the herd prevalence of MAP infection in sheep flocks was estimated to be 21.1% [49]. Seroprevalence study of MAP infection in goat dairy flocks in France revealed an apparent and estimated true prevalence of 55.2% and 62.9% at herd level, while at individual animal level they were 2.9% and 6.6%, respectively [50].…”
Section: Discussionmentioning
confidence: 99%